2001
DOI: 10.54991/jop.2001.1801
|View full text |Cite
|
Sign up to set email alerts
|

Climatic implications of tree-ring density variations in Himalayan conifers

Abstract: The densitometric analysis of Himalayan conifers from six different sites reveals the strong association of ring density parameters with regional climate. Minimum earlywood density and total ring width are major contributors to the tree growth-climate relationship. It also indicates that pre-monsoon (March-April-May) temperature has significant positive relationship with earlywood density and significant negative correlation with total ring width. In case of precipitation, earlywood density gives negative rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Pre-monsoon precipitation, however, was negatively correlated with earlywood density but positively correlated with ring width. In contrary, latewood density did not show any coherent relationship with climate (Borgaonkar et al 2001).…”
Section: Himalayamentioning
confidence: 58%
“…Pre-monsoon precipitation, however, was negatively correlated with earlywood density but positively correlated with ring width. In contrary, latewood density did not show any coherent relationship with climate (Borgaonkar et al 2001).…”
Section: Himalayamentioning
confidence: 58%
“…the ratio between the weight and volume of a piece of wood) to micrometre precision (Pagotto et al, 2017;Polge, 1970;Schweingruber et al, 1978). The potential of wood density parameters such as MXD for dendroclimatic research using coniferous species was noted in the late 1990s in the Himalaya (Borgaonkar et al, 2001;Hughes, 1992Hughes, , 2001Pant et al, 2000). Both the MXD and MND are strongly influenced by pre-monsoon summer climate.…”
Section: Maximum Latewood Densitymentioning
confidence: 99%
“…For instance, the MXD of C. deodara from the western Himalaya appears to be positively correlated with pre-monsoon temperature ( r = 0.39, p < .01 ) and precipitation ( r = 0.41, p < .01 ) between March and May (Pant et al, 2000). Although the climatic responses vary for different species and from place to place, studies show that compared to MXD, the MND records stronger climate signals in the western Himalaya (Borgaonkar et al, 2001). In the Kashmir valley, Hughes (2001) found that the relationship between MXD and temperature became weaker from the middle of the 20 th century, but no long-term trend was observed.…”
Section: Future Tree-ring Research Directions In the Himalayamentioning
confidence: 99%